Peatland Fire Danger Rating According to Weeds Characteristic Under Jelutung (Dyera Polyphylla) Plantation - Acep Akbar (Center for Journal Management and Publication, 2016)
Besides to be a competitor plant, weeds could act as the potential fuel under plantation forest in peatland. Characteristic of weeds in relation to peat swamp forest fire danger was studied under jelutungÂ plantation in Central Kalimantan. The research was aimed at exploring the potency of weed to become one of the fire danger rating indicators. By using vegetation analyses method in sampling unit of weeds population, results showed that three plantation area have different dominance weed species. The weeds species that could be the indicator of height fire risk according to water content and percentage of weed mortality during the drought, height potency of greenhouse gas emmision, culm height, and chemical material content that easy burned in this study were Imperata cylindrica, Stenochlaena polustris, Cyclosorus aridus, and Nephrolepis exaltata. While, the presence of Glichenia linearis, Melastoma malabatracum, Ficus grossulariodes, Saurophus androginus, Spatoglathis plicata,Himenocalis littoralis, Leptaspis urcheolata, Cyperus rotundus, and Amaranthus spinosa were not indicated high fire risk.